Formalismo de Hamilton-Jacobi à la Carathéodory. Parte 2: Sistemas singulares - Bertin, M. G. [UNESP]; Pimentel, B. M. [UNESP]; Pompeia, P. J. (My University, 2008)
In the second part of the paper published on Revista Brasileira de Ensino de Física 29, 393 (2007) we will show how the Hamilton-Jacobi formalism works for singular systems. We will bring the generalization of the Carathéodory's method for Lagrangians whose Hessian matrix is singular. We will also build a procedure of constraint analysis of such systems based on the formalism.
The Hamilton-Jacobi formalism à la Carathéodory. Part 2: Singular systems
Keywords: Constraints; Hamilton-Jacobi equation; Singular systems